Primary Ovarian Pregnancy after Interval Tubal Ligation- An Unexpected Conception at an Unusual Location - Musale, Madhavi Omdeorao; Rudrappa, Prashanth; M, Udaya Kumar; Subramanian, Ramaswamy Anikode (Annals of Pathology and Laboratory Medicine, 2019)
Ovarian pregnancy constitutes <3% of all ectopic pregnancies with an incidence ranging from 1:6,000 to 1:40,000 pregnancies. Ovarian ectopic pregnancy is a very rare occurrence after the interval tubal ligation. A 25 year old multi gravida, post tubectomised woman presented with acute lower abdominal pain with history of interval sterilisation after 4 months of last child birth. Ultrasonography detected a seven weeks gestation with cardiac activity in right adnexa with no evidence of intrauterine pregnancy. Right salpingo-oopherectomy with removal of an unruptured pregnancy from the right ovary was done by exploratory laparotomy. On histopathological examination, chorionic villi within the ovarian stroma was seen. Though ovarian pregnancy is rare, one has to consider the possibility of an ectopic gestation even in post interval tubal-ligation cases. This would help in early diagnosis and reduce the rate of maternal morbidity and mortality.